Pyrogeography, historical ecology, and the human dimensions of fire regimes. (24th February 2014) - Roos, Christopher I.; Bowman, David M. J. S.; Balch, Jennifer K.; Artaxo, Paulo; Bond, William J.; Cochrane, Mark; D'Antonio, Carla M.; DeFries, Ruth; Mack, Michelle; Johnston, Fay H.; Krawchuk, Meg A.; Kull, Christian A.; et al.
Abstract In our 2011 synthesis (Bowman et al., Journal of Biogeography, 2011, 38, 2223–2236), we argued for a holistic approach to human issues in fire science that we term 'pyrogeography'. Coughlan & Petty (Journal of Biogeography, 2013, 40, 1010–1012) critiqued our paper on the grounds that our 'pyric phase' model was built on outdated views of cultural development, claiming we developed it to be the unifying explanatory framework for all human–fire sciences. Rather, they suggest that 'historical ecology' could provide such a framework. We used the 'pyric transition' for multiple purposes but did not offer it as an exclusive explanatory framework for pyrogeography. Although 'historical ecology' is one of many useful approaches to studying human–fire relationships, scholars should also look to political and evolutionary ecology, ecosystems and complexity theories, as well as empirical generalizations to build an interdisciplinary fire science that incorporates human, ecological and biophysical dimensions of fire regimes.